The influence of anthropometric variables on the performance of elite traditional rowers - Castañeda-Babarro, A.; León-Guereño, P.; Viribay, A.; Gutiérrez-Santamaría, B.; López, I.; Mielgo-Ayuso, J. (Sports, 2024)
Athletes` anthropometry, and especially their body composition, plays an important role in sport performance in general and in Trainera rowing in particular. Rowers` anthropometric and performance profiles may vary according to their position in the boat. The objectives of this study were to investigate the relationship between anthropometry, physical performance, physiological variables, and elite male rowers` boat positions. Twenty elite male traditional rowers were assessed and categorized according to their boat position: either in the middle of the boat (M) (n = 9) or in the bow and stern positions (BS) (n = 11). Anthropometric measurements and body composition were obtained for each rower, and physical performance was measured by a 45-s supramaximal rowing test and a VO2max incremental test on a Concept II rowing ergometer. The results showed that the rowers in the middle were taller (186.6 ± 4.9 cm), and significant differences were also found between the two groups according to body mass (BS 72.3 ± 3.8 vs. M 85.4 ± 4.3) and peak power (BS 641.5 ± 84 vs. M 737 ± 47.1), mean power (BS 538.5 ± 48.4 vs. M 604.1 ± 42.3), and physiological parameters (p < 0.05), VO2max (BS 66.5 ± 4.9 vs. M 59.3 ± 6.7). It can be concluded that height could be associated with elite rowers` performance and that a lower body mass index is related to better performance in bow and stern positions.